Experiences of assessment in face-to-face and online courses of Portuguese as a foreign language in a language and teacher development centre - Consolo, Douglas Altamiro (Cadernos de Linguagem e Sociedade, 2026)
This paper focuses on proficiency assessment in courses of Portuguese as a foreign language (PFL), considering both context types: face-to-face and online lessons. Online courses have become more frequent because of the restrictions imposed on face-to-face encounters by COVID-19, but also thanks to advantages of remote teaching and the use of technology in education. Assessment is an essential component of the three-part structure assessment, learning and teaching, considering washback effects of assessment in the teaching process. The experiences presented here happened in the context of a Center for Languages and Teacher Education (CLDP), an extension project developed in the three campi of São Paulo State University (UNESP) in Brazil, where undergraduates in Letters courses can act as language teachers. A placement test, examples of written test tasks and an oral activity to assess PFL students are presented, to illustrate possibilities to verify language development and proficiency, and contribute to the development of assessment tools.